Low-cost system for programming by demonstration grasp of objects in robotics (Revista de Investigaciones Universidad del Quindío, 2014)
We present the implementation and results obtained from preliminary tests in a low-cost system, which allows the signals acquisition of the grasp of objects in robotics. The system is composed of a data glove and a robotic hand with three fingers. The data glove is our own make and it has force and position sensors. The signals obtained are saved for later reproduction. The robotic hand was developed with rapid prototyping. The developed system resents low cost compared with the commercial systems. Besides, it can be easily duplicated because of the commercial elements that compose it. The results show the operation of the developed system.
Keywords: Data glove; force sensor; flexion sensor